Exploring Digital Frontiers in Islamic Social Finance Campaigns: An Extensive Netnographic Analysis of Kemensos RI - Fadilla Okta Kurniawati; Muhamad Subhi Apriantoro (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study examines the implementation of modern digital campaigns in Islamic social finance within the context of Islamic marketing, highlighting their theoretical and practical significance in addressing social and economic challenges. Methodology: A qualitative case study approach was employed, focusing on KEMENSOS RI as a representative Islamic social finance institution. Data were collected using a netnographic method by analyzing 102 social media posts from Facebook, Instagram, Twitter, and YouTube. The analysis was conducted using NVivo 12 Plus to code and identify dominant themes and campaign strategies. Results: The findings demonstrate that KEMENSOS RI implements digital Islamic social finance campaigns through integrated communication strategies. Five main parent nodes were identified: (1) live assistance, (2) online news dissemination, (3) roadshows, (4) workshops, and (5) training programs. These approaches reflect a structured digital engagement model aimed at increasing public awareness and participation. The results also indicate a growing public interest in Islamic social finance as an effective instrument for addressing poverty, promoting economic growth, and strengthening social welfare, particularly in Muslim-majority countries. Applications/Originality/Value :This study provides original empirical evidence on digital Islamic social finance campaigns, an area that remains limited in Islamic marketing research. The findings offer practical insights for policymakers and practitioners in designing effective digital-based social finance strategies, while also contributing to the theoretical understanding of the role of Islamic social finance in sustainable social and economic development.